Potential application of submerged horizontal plate as a wave energy breakwater: A 2D study using the WCSPH method. (1st August 2019) - He, Ming; Gao, Xifeng; Xu, Wanhai; Ren, Bing; Wang, Hongshu
Abstract: The submerged horizontal plate (SHP) has been extensively studied as an open-type breakwater, and some research explored its potential as a wave energy converter. However, these two functionalities were seldom combined in the literature. In this study, a 2D numerical model solving the wave-SHP interaction was built by using the weakly compressible smoothed particle hydrodynamics (WCSPH) method. The thin-walled boundary condition was verified through a dam-break impact case. The accuracy of wave profile and flow velocity calculations was validated by comparing with available experiments of solitary and regular waves interactions with SHPs. Comparison of the wave dynamic and flow dynamic between SHP and submerged step were made, which showed the advantages and disadvantages of the SHP. Then a parametric study of regular waves-fixed SHP interaction was conducted. Empirical formulas for the wave transmission coefficient and energy conversion efficiency were obtained by regressing numerical results using the Levenberg-Marquardt algorithm. Finally, a mathematical programming problem concerning the combined functionalities of SHP was established. Using the complex method, the optimal length and submergence of SHP regarding different emphases taken on the regular wave attenuation and energy utilization were solved. The results preliminarily demonstrated the potential application of SHP as a wave energy breakwater and provided reference on its parameter design, although this work was carried out in 2D and ignored the effects of energy convertor and piles on wave and flow patterns. Highlights: The WCSPH method is used to simulate the wave-submerged horizontal plate (SHP) interaction. The numerical model is validated through numerical tests and available experiments. Formulas for the wave transmission coefficient and energy conversion efficiency of SHP are obtained. The optimal configuration and performance of the SHP-type wave energy breakwater are discussed.